A STUDY ON BEHAVIORAL ALTERATIONS INDUCED BY CADMIUM CHLORIDE IN A FRESHWATER FIELD CRAB Barytelphusa guerini - SIDDIQUI, AKHTER ALI; AFSHAN, MALIHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The behavioral profile of aquatic animals exposed to diverse toxicants is considered as an index to estimate the degree and nature of stress experienced by the animals both in natural and in experimental conditions. Acute toxic effects and behavioral alterations induced by exposure of the freshwater crab Barytelphusa guerini to cadmium chloride reported after finding Lc50. Ten healthy specimens of the same size in each group were exposed to seven different concentrations of cadmium chloride (1.00, 1.25, 1.50, 1.75, 2.00., 2.25 and 2.50 µg/L) along with a control group for 0 to 96 hours. The exposed crabs exhibited hyperactivity, escape behavior, increased scaphognathite beating, topsy-turving reflexes, increased oxygen consumption, tendency of avoiding, hypersecretion of mucus and release of excess excretory product ammonia with increasing toxicant concentration and exposure time. Toxin induced alteration of studied behavior is an indicative of a possible shift in the overall physiological functions and biological activities, of this experimental animal in its natural habitat.